Pengaruh Latihan Pull-Up Dan Latihan Beban Media Karet Terhadap Kemampuan Lemparan Atlet Lempar Lembing - Hasni Mubaraq; Wilda Welis; Liza Liza (JURNAL STAMINA, 2022)
Writing this journal is done to determine the effect of pull-up training and rubber weight training on the throwing ability of the Saribu Rumah Gadang (SRG) javelin throwing athletes in South Solok. The problem in this study is the lack of the throwing ability of the Saribu Rumah Gadang (SRG) javelin throwing athletes in South Solok. This study aims to determine the effect of pull-up training and rubber weight training on throwing ability. This research is an experimental research. This research was conducted in February-March 2021 which was carried out in the Bancau Koto Baru Solok Selatan field. The population in this study were 10 athletes. Sampling in this study using total sampling technique, so that the number of samples in this study were 10 athletes. The research instrument used the hop step style javelin throw test. The data analysis technique used t test analysis. The results of this study show that pull-up training and weight training with rubber media have an effect on the throwing ability of Saribu Rumah Gadang (SRG) javelin throwing athletes in South Solok. Tcount> ttable (2,98 > 1,83). Where from the average throwing ability of 29.28 increased to 35,96 (increased by 6.68).